PERTANGGUNGJAWABAN NAKHODA DI ATAS KAPAL MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN - Barit Barit (Universitas 17 Agustus 1945 Samarinda, 2020)
AbstractThe master is the highest leader on the ship. The master has a great responsibility for the safety of everyone and even the cargo on board. In the event of an accident that causes the victim to fall, the skipper may be subject to criminal liability based on Law Number 17 of 2008 concerning Sailing. The responsibility of the skipper for the safety of the voyage according to Law Number 17 of 2008 concerning Shipping occurs if the skipper is proven guilty or negligent in carrying out his duties and obligations, resulting in a ship accident that harms the service user. If due to an error or negligence the skipper results in the death of another person, the skipper is threatened with criminal sanctions in accordance with the error/neglect. Criminal sanctions for negligent skipper on shipping safety accor-ding to Law Number 17 of 2008 concerning Sailing, in the form of imprisonment and fines. Keywords : Helmsman, Responsibility, Safety, Shipping